How useful are ferric chloride models of arterial thrombosis?. (18th May 2020) - Grover, Steven P.; Mackman, Nigel
Abstract: The ferric chloride models of arterial thrombosis are useful tools with which to investigate the cellular and molecular mechanisms that contribute to arterial thrombosis. Recent insights have, however, revealed the complex and multifaceted mechanism by which ferric chloride induces thrombus formation. Here, we discuss the strengths and weaknesses of the ferric chloride models of arterial thrombosis. Particular focus is given to the phenotypes of different knockout mice in the ferric chloride models and how these compare to other models with independent modes of initiation. Further, we discuss the relevance of the ferric chloride models to the human pathology of atherothrombotic disease.